IMPLEMENTATION OF PRUDENTIAL PRINCIPLES AND RISK MANAGEMENT IN SHARIA BANK FINANCIAL MANAGEMENT (CASE STUDY OF INDONESIAN SHARIA BANK) - Dwini Apriantami; Aliyah Tulhimma; Rosya Ilma Nafiah; Nova Rahma Daniarti; Putri Deswita; Muchlis Ramananda; Dwi Ilmi Kayana; Harmeindah Prameska (CV. Era Digital Nusantara, 2023)
This study aims to analyze the application of prudential principles and risk management in the financial management of Islamic banks by conducting case studies on Islamic banks in Indonesia. Islamic banks have the unique characteristic of having to adhere to Islamic principles in all aspects of their operations, including financial management. Prudence becomes very important in Islamic banks to ensure the sustainability and stability of their operations. In this context, risk management has an important role in identifying, evaluating, and managing the risks associated with Islamic banking activities. This study focuses on risk management related to financial aspects, including credit risk, liquidity risk, market risk and operational risk. Analysis is conducted to assess the level of application of prudential principles and risk management by Islamic banks in financial management. The results of the study show that Islamic banks in Indonesia generally use the principle of prudence and risk management in managing their finances.